Genetic studies on the Cayo Santiago rhesus macaques: A review of 40 years of research. Issue 1 (1st June 2015) - Widdig, Anja; Kessler, Matthew J.; Bercovitch, Fred B.; Berard, John D.; Duggleby, Christine; Nürnberg, Peter; Rawlins, Richard G.; Sauermann, Ulrike; Wang, Qian; Krawczak, Michael; Schmidtke, Jörg
Abstract : Genetic studies not only contribute substantially to our current understanding of the natural variation in behavior and health in many species, they also provide the basis of numerous in vivo models of human traits. Despite the many challenges posed by the high level of biological and social complexity, a long lifespan and difficult access in the field, genetic studies of primates are particularly rewarding because of the close evolutionary relatedness of these species to humans. The free‐ranging rhesus macaque ( Macaca mulatta ) population on Cayo Santiago (CS), Puerto Rico, provides a unique resource in this respect because several of the abovementioned caveats are of either minor importance there, or lacking altogether, thereby allowing long‐term genetic research in a primate population under constant surveillance since 1956. This review summarizes more than 40 years of genetic research carried out on CS, from early blood group typing and the genetic characterization of skeletal material via population‐wide paternity testing with DNA fingerprints and short tandem repeats (STRs) to the analysis of the highly polymorphic DQB1 locus within the major histocompatibility complex (MHC). The results of the paternity studies also facilitated subsequent studies of male dominance and other factors influencing male reproductive success, of male reproductive skew, paternal kin bias, and mechanisms of paternal kin recognition. More recently, the CS macaques have been the subjects of functional genetic and gene expression analyses and have played an important role in behavioral and quantitative genetic studies. In addition, the CS colony has been used as a natural model for human adult‐onset macular degeneration, glaucoma, and circadian rhythm disorder. Our review finishes off with a discussion of potential future directions of research on CS, including the transition from STRs to single nucleotide polymorphism (SNP) typing and whole genome sequencing. Am. J. Primatol. 78:44–62, 2016. © 2016 Wiley Periodicals, Inc.